How Accurately Can Religious Educators Predict Student Achievement?. Issue 2 (3rd April 2021) - Lyons, Kyle; Thiede, Keith; Osguthorpe, Richard D.
Abstract: Teachers make a variety of judgments as they teach. The accuracy of these judgments may influence instruction and student achievement. This study examined how accurately religious educators judge student learning, what cues they report using to make judgements, and how cue utilization affected their accuracy. Judgment accuracy was greater for teachers who reported using cues related to class performance than for those who did not. Judgment accuracy was greater for those who did not report using personal attributes as a cue than for those who did. These results are explained in the context of the cue-utilization framework.